Radiation-Induced Leiomyosarcoma: Does Antimetabolite Chemotherapy Contribute? A Report of Three Cases. (2003) - Brockstein, Bruce; Mundt, Arno; Haraf, Daniel J.; Ferguson, Mark; Montag, Anthony
Abstract : Purpose: Radiation therapy in low and high doses is known to be associated with the occurrence of late secondary sarcomas. The addition of chemotherapy has not been clearly demonstrated as a contributing factor. We describe three patients with radiation-associated leiomyosarcoma who had also received antimetabolite chemotherapy. Methods: Three cases of leiomyosarcoma occurring 9–27 years after radiation and antimetabolite chemotherapy are presented, along with histopathological details. A Medline search was used to assess prior reports of leiomyosarcoma after radiation. Results: These three cases appear to be the first reported in which leiomyosarcoma followed therapy with radiation and antimetabolites. Discussion: With the increasing use of antimetabolite therapy combined with radiation, there is the potential for more occurrences of leiomyosarcoma or other post-treatment sarcomas.